2023
DOI: 10.1002/idm2.12059
|View full text |Cite
|
Sign up to set email alerts
|

Acidic oxygen evolution reaction: Mechanism, catalyst classification, and enhancement strategies

Abstract: As the most desirable hydrogen production device, the highly efficient acidic proton exchange membrane water electrolyzers (PEMWE) are severely limited by the sluggish kinetics of oxygen evolution reaction (OER) at the anode. Rutile IrO2 is a commercial acid‐stable OER catalyst with poor activity and high cost, which has motivated the development of alternatives. However, hitherto most of the designed acidic OER catalysts have disadvantages of low activity or stability, which cannot meet the requirement of ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 230 publications
(350 reference statements)
0
33
0
Order By: Relevance
“…To direct the forthcoming studies on CPs, a prospect is provided as follows: At first, the synthesis technique of CPs requires upgrading to better align with electrocatalytic applications, such as nanoscaling, increasing specific surface area, and tailoring electronic structure. [132][133][134] Secondly, the electrocatalytic performance of CPs should be appropriately correlated with the implanted transition-metal cations into structural cavities, which would in situ occur and alter the redox behavior of active sites. 133 Comparing the structure-activity relationships in various CPs is also beneficial to comprehend the correlations between the active sites and catalytic activity.…”
Section: Discussionmentioning
confidence: 99%
“…To direct the forthcoming studies on CPs, a prospect is provided as follows: At first, the synthesis technique of CPs requires upgrading to better align with electrocatalytic applications, such as nanoscaling, increasing specific surface area, and tailoring electronic structure. [132][133][134] Secondly, the electrocatalytic performance of CPs should be appropriately correlated with the implanted transition-metal cations into structural cavities, which would in situ occur and alter the redox behavior of active sites. 133 Comparing the structure-activity relationships in various CPs is also beneficial to comprehend the correlations between the active sites and catalytic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported various strategies, such as lattice oxygen stabilization and self-healing, for 3d transition metals to maintain their OER activity in an acid medium. 25,[32][33][34][35][36] However, these strategies should be correctly selected to avoid interference with CO 2 RR activity. For example, ions in the anolyte used for the self-healing strategy can decrease the selectivity during CO 2 RR.…”
Section: Phenomenon Occurring At the Ni-based Electrode In The Co 2 M...mentioning
confidence: 99%
“…Dispersing active particles on stable metal oxide supports like doped tin oxides, 16,17 manganese oxides, 18,19 and tricobalt tetroxides 20,21 is a promising way to approach the above needs for OER electrocatalysts, 22 interactions with surface-supported noble metals. 23 However, most of the inert supports are synthesized in laboratories by corresponding precursors to introduce doping elements or modify surface morphology, which make the whole process more complicated. To a simplified synthesis method, commercial titania (TiO 2 ), having already been used in photocatalytic and commercialized in chlorine-alkali electrolysis, 24 is another prospective support owing to its advantages such as having rich sources and being dimension-stable against anodic corrosion.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Hence, extensive efforts to modify RuO 2 electrocatalysts have been given to improve the activity and stability, as well as reduce the cost. Dispersing active particles on stable metal oxide supports like doped tin oxides, , manganese oxides, , and tricobalt tetroxides , is a promising way to approach the above needs for OER electrocatalysts, due to good corrosion resistance for support and electronic coupling interactions with surface-supported noble metals . However, most of the inert supports are synthesized in laboratories by corresponding precursors to introduce doping elements or modify surface morphology, which make the whole process more complicated.…”
Section: Introductionmentioning
confidence: 99%